Uji Trend Cox-Stuart Pada Kunjungan Wisatawan di Tapanuli Tengah Tahun 2023 - Preydes Xaviera Sitorus; Septa Yohana Lubis; Yohana Yulia Purba (Interdisciplinary Explorations in Research Journal, 2024)
The tourism sector plays a significant role in the economic growth of every region, including Tapanuli Tengah Regency, which is renowned for its natural beauty and cultural richness. Using the Cox-Stuart Test, this study attempts to identify visitor trends to Tapanuli Tengah throughout the year 2023. The non-parametric analysis process is used to collect data on the number of tourist visits from the Central Statistics Agency (BPS). This method determines whether the number of visits is increasing, decreasing, or stable by comparing the initial and most recent observations from the monthly time series data. The analysis results show that there is not enough evidence to say that the tourist trend in Tapanuli Tengah will decrease in 2023. This research provides important guidance for policymakers in creating tourism management and promotion strategies in Tapanuli Tengah Regency.